2006
DOI: 10.1097/01.inf.0000225786.00940.37
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution Syndrome From Nontuberculous Mycobacterial Infection After Initiation of Antiretroviral Therapy in Children With Hiv Infection

Abstract: The immune reconstitution syndrome caused by nontuberculous mycobacterial (NTM) infection is reported in 9 of 153 HIV-infected children 2 to 26 weeks after initiation of antiretroviral therapy. The clinical syndrome included fever and dyspnea (2 children), fever and abdominal pain (3), subcutaneous nodules or suppurative lymphadenitis (4). The causative species were Mycobacterium avium (4), Mycobacterium scrofulaceum (3), Mycobacterium kansasii (1) and Mycobacterium simiae (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 18 publications
(8 reference statements)
0
19
2
Order By: Relevance
“…In-vitro data imply that there is an increase in antimycobacterial immune responses in HIV-infected children receiving HAART [60 ]. Also, IRIS in children has been associated with nontuberculous mycobacteria [61 ] and previous BCG vaccination [62][63][64].…”
Section: Immune Reconstitution Inflammatory Syndromementioning
confidence: 99%
“…In-vitro data imply that there is an increase in antimycobacterial immune responses in HIV-infected children receiving HAART [60 ]. Also, IRIS in children has been associated with nontuberculous mycobacteria [61 ] and previous BCG vaccination [62][63][64].…”
Section: Immune Reconstitution Inflammatory Syndromementioning
confidence: 99%
“…Diagnosis was suspected given a CD4 cell count rise from 4 to 236 cells/μl. The patient survived following a regimen including a quinolone, macrolide and prednisolone, with temporary HAART cessation 8. Although other NTM can be successfully treated with just three drugs, some cases do require a fourth agent, and given the relative lack of treatment data for M simiae along with the positive CSF culture, we chose four drugs over three, including rifabutin and a fluoroquinolone.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary disease due to IRIS associated with M. kansasii was also reported, in only 2 cases. 10 Puthanakit et al 9 observed IRIS due to acid-fast bacilli in 9 (4 due to MAC, 3 due to M. scrofulaceum, 1 due to M. simiae, and 1 due to M. kansasii) of 153 children with AIDS.…”
Section: Case Reportmentioning
confidence: 97%
“…8 There have been very few reports of IRIS caused by M. kansasii. 9 Lawn et al 10 identifi ed 25 articles describing 64 cases of MAC-associated IRIS, and 27 articles describing 86 cases of TB-associated IRIS. On the other hand, IRIS associated with other nontuberculous mycobacteria was infrequent and was described in only 16 patients.…”
Section: Case Reportmentioning
confidence: 98%